NUTRIENTS' DEFICIENCY RISKS IN PREGNANT WOMEN DUE TO THEIR EATING HABITS - Rositsa Chamova; Maria Panteleeva (Peytchinski Publishing, 2024)
Aim: To research the dietary habits of pregnant women living in Bulgaria and to assess the possible health effects for the offspring. Methods: An online anonymous survey of the dietary habits of pregnant women living in Bulgaria was conducted. A questionnaire was developed in Google Forms, collecting information about the demographic profile, diet, frequency of consumption of certain food and drink groups, use of alternative dietary patterns, etc. The questionnaire was spread through social media using the snowball technique. The assessment of the respondents' dietary habits was based on the national dietary recommendations during pregnancy. Descriptive analysis of the results was done using Jamovi software statistical package ver. 2.3.0. Results: 117 pregnant women aged between 21 and 54 years (median - 30 years) were interviewed. Daily consumption of milk and dairy products was found in 41% and 47% of respondents, respectively. Among the women surveyed, all were reported to consume dairy products, except 5.1% who did not consume milk. The relative share of women who rarely or never consumed fish was 58.1% and 12%, respectively, and one woman did not consume both fish and meat. Vegetarians accounted for 6% of the women surveyed, and 6% were on a low carbohydrate diet. Conclusion: Although the majority of pregnant women surveyed followed the recommendations for healthy eating, some rarely or never consumed some of the healthy foods, which put them at risk of deficiency or insufficiency of certain nutrients.